SPEECH ACTS USED BY A GAMING YOUTUBER IN AN ONLINE GAME VIDEO - Nini Ibrahim; Ummul Qura (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
The purpose of this study was to determine the speech acts strategies used by a gaming Youtuber, Jess No Limit in one of his online-game streaming videos. A mixed-method research design was employed by combining the qualitative and quantitative approaches to data collection and data analysis. The results of this study suggest that a gaming Youtuber most likely use positive politeness strategies to seek agreement, pay attention to his interests, wants or needs, giving away rewards, engaging the viewers in his activities, provide reasons and intensify attention to the speaker. This positive politeness strategy is a You-tuber's strength in communicating to pique the audience's interest and sympathy and gain as many subscribers as possible.